Effects of different ageing methods on colour, yield, oxidation and sensory qualities of Australian beef loins consumed in Australia and Japan. (November 2019) - Ha, Minh; McGilchrist, Peter; Polkinghorne, Rod; Huynh, Long; Galletly, Joanne; Kobayashi, Kuniyuki; Nishimura, Takanori; Bonney, Steve; Kelman, Khama R.; Warner, Robyn D.
Abstract: This study investigated the effect of three ageing methods (dry, wet and stepwise wet-then-dry) and ageing time on pH, colour, yield, lipid and protein oxidation and eating quality of beef loins using Meat Standards Australia (MSA) sensory protocols with 900 and 540 consumers in Australia and Japan, respectively. Australian beef loins ( Longissimus thoracis et lumborum ) at four days post mortem were subjected to wet ageing (boneless; for 7, 21, 35 or 56 days), dry ageing (bone-in; for 35 or 56 days) or a wet-then-dry ageing method (bone-in; 21 days wet ageing followed by 35 days dry ageing). The pH was higher in dry aged than wet aged beef loins ( P < .001). Instrumental measurement of surface colour of trimmed dry and wet aged steaks showed significant differences in a*, b* and hue angle. Weight loss was higher in dry aged primals (P < .001), however, total water content was similar among the two ageing methods ( P = .934). Retail yield did not differ between 35 and 56 days dry aged primals. Lipid (TBARS) and protein (total carbonyl content) oxidation between the dry and wet aged samples differed depending on the ageing time. When comparing the wet-then-dry and 56 days dry aged samples, only pH and retail yield differed. Australian and Japanese consumers rated dry aged steaks significantly higher ( P < .001) than the wet aged counterparts for tenderness, juiciness, flavour, overall liking and weighted palatability scores. The wet-then-dry steaks were also rated higher than the 56 days wet aged steaks for flavour, overall liking and palatability within the Japanese sensory panels. The Japanese consumers also consistently rated all MSA sensory attributes lower ( P < .001) than the Australian consumers. The results from this study show dry ageing provides a value adding opportunity for the meat industry in both domestic and export markets. Graphical abstract: Unlabelled Image Highlights: Dry ageing resulted in beef loins with higher pH and more desirable colour compared to wet ageing. Dry and stepwise ageing resulted in beef with similar physical and chemical properties. Australian and Japanese consumers preferred dry aged and stepwise aged beef to wet aged products. 21 days and 35 days are recommended for wet and dry ageing, respectively, to maximise palatability.